A Histopathologically Diagnosed Neurocysticercosis Case from Turkiye - Ozer Balin, Safak; Enez, Murat; Akbulut, Ayhan; Calik, Muhammet; Akgun, Bekir; Balgetir, Ferhat; Yildirim, Hanefi (Ankara Microbiology Soc, 2022)
Cysticercosis is a parasitic tissue infection caused by larval cysts of Taenia solium. Although the disease affects many tissues, it primarily affects the brain and muscles. The most common form is neurocysticercosis, a term used for human central nervous system involvement with T.solium cysts. Neurocysticercosis is an important public health problem in many parts of the world. Its prevalence is particularly high in places where T.solium tapeworms are common, such as Mexico, Central America, South America, Southeast Asia, Africa, China, India, and Nepal. Its incidence has been increasing rapidly in recent years in non-endemic countries, due to both import and local cases, while in some highly endemic areas, numbers appear to have decreased, possibly due to better sanitation and increased public awareness. It is extremely rare in Turkiye. Cysticercosis is usually caused by drinking water or eating food containing tapeworm eggs. Clinical manifestations can range from completely asymptomatic infection to severe illness or death. Although the infection can involve any part of the central nervous system, symptomatic patients mostly have spinal cord involvement, intracerebral lesion, intraventricular cyst or subarachnoid lesion. An intraparenchymal cerebral cyst typically grows slowly and causes minimal symptoms for years or decades after the onset of infection. The site of involvement and the symptoms experienced determine the diagnosis and treatment method. The current general consensus supports antihelmintic and corticosteroid therapy for viable parenchymal lesions. In this report, a neurocysticercosis case with a single brain lesion that was surgically removed and histologically examined was presented. The patient had complaints of lisp in the tongue, numbness in the lips and left face. The patient had no concomitant chronic disease. The patient did not have a travel history or a history of eating pork but had a history of contact with a dead pig two months ago. Upon detection of a central mass in the brain computed tomography examination, surgical procedure was performed on the patient. Based on the identification of a larval stage of T.solium in biopsy material neurocysticercosis was diagnosed. However, histopathologically demonstration of the parasite is not possible in most cases. The patient received an antiparasitic treatment with albendazole 1000 mg/d in combination with dexamethasone. The patient was successfully treated and is still being followed up by calling for controls.
Türkiye’de Histopatolojik Olarak Tanısı Konulmuş Bir Nörosistiserkoz Olgusu
Keywords: Neurocysticercosis; Taenia solium; T?rkiye